APPLICATION OF THE CDIO APPROACH TO THREE LEVEL ENGINEERING PROGRAMS DESIGN - Alexander I. Chuchalin (Высшее образование в России)
Some results of an analysis and evaluation of the CDIO Syllabus topicality for the level engineering programs (BEng, MSc and PhD) design are presented. The analysis is based on a comparison of the CDIO Syllabus v2 intended learning outcomes with the requirements to preparation of the various engineering program graduates to complex, innovative and research activities. The requirements are defined taking into consideration the Russian Federal State Educational Standards and the Association for Engineering Education of Russia criteria, harmonized with the international standards. The results of an examination of the CDIO Syllabus v2 made by trainees of the Russian CDIO Academy are used.